Illiquidity and volatility spillover effects in equity markets during and after the global financial crisis: An MEM approach - Yongdeng Xu; Nicholas Taylor; Wenna Lu (Cardiff University, Cardiff Business School, 2018)
Even though volatility spillover effects in global equity markets have been documented extensively, the transmission of illiquidity across national borders has not. In this paper, we propose a multiplicative error model (MEM) for the dynamics of illiquidity. We empirically study the illiquidity and volatility spillover effects in eight developed equity markets during and after the recent financial crisis. The results indicate that equity markets are interdependent, both in terms of volatility and illiquidity. Most markets show an increase in volatility and illiquidity spillover effects during the crisis. Furthermore, we find volatility and illiquidity transmission are highly relevant. Illiquidity is a more important channel than volatility in propagating the shocks in equity markets. Our results show an overall crucial role for illiquidity in the US market in influencing other equity markets' illiquidity and volatility. These findings are of importance for policy makers as well as institutional and private investors.
Keywords: C32; C52; G14; 330; Illiquidity Spillover; Volatility Spillover; Multiplicative Error Model